THE EFFECT OF MEDIA COMBINATION TO THE GROWTH OF Coelogyne pandurata ORCHID ON ACLIMATED STAGES - RISKA MASYURA; ASNAWATI ASNAWATI; AGUSTINA LISTIAWATI (Jurnal Sains Pertanian Equator, 2018)
Acclimatization is a stage of conditioning the plan of multiplication through invitro to invivo environment. The success of acclimatization depends on the growth media that is appropriate to the type and nature of orchids. This study aims to find the best combination of growth media acclimatization of Coelogyne pandurata orchids. The study was conducted at the shelter house Green Villa of the Faculty of Agriculture of University of Tanjungpura Pontianak for 4 months. It was starting from August 11th, 2017 to December 10th, 2017. The study used a Completely Randomized Design (RAL), consisting of 6 treatment levels, 4 replicates and each treatment unit consisting of 4 plants. Observational variables included live percentage, number of leaves, leaf length increase, number of buds, and number of root, root length and environmental observation. The results showed that the combination treatment of growth media for the growth of Coelogyne pandurata orchid had significant effect on the number of shoots and had no significant effect on the percentage of live, number of leaves,  the increase of leaf length, number of root and root length. Based on the research, it can be concluded that all combinations media provide live percentage of more than 80% and the combination of coconut fiber and fern gives the best result the number of  buds that is 2,56 buds.Keywords: Acclimatization, Coelogyne pandurata Orchid, Combination of Media.